2016
DOI: 10.1111/evo.13061
|View full text |Cite
|
Sign up to set email alerts
|

One stimulus-Two responses: Host and parasite life-history variation in response to environmental stress

Abstract: Climate change stressors will place different selective pressures on both parasites and their hosts, forcing individuals to modify their life-history strategies and altering the distribution and prevalence of disease. Few studies have investigated whether parasites are able to respond to host stress and respond by varying their reproductive schedules. Additionally, multiple environmental stressors can limit the ability of a host to respond adaptively to parasite infection. This study compared both host and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Furthermore, the p38 MAPK pathway is linked to the positive regulation of egg‐laying behavior in C. elegans (Kim et al, ), providing a mechanism by which it may mediate fecundity compensation. Interestingly, although hosts in the Biomphalaria glabrata–Schistosoma mansoni trematode system do not exhibit fecundity compensation during presumably stressful drought conditions, the parasites do ramp up offspring production (Gleichsner, Cleveland, & Minchella, ). Such a finding suggests that the connection between general stress and fecundity compensation can be complex in natural systems and that it can nevertheless be extended beyond hosts to parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the p38 MAPK pathway is linked to the positive regulation of egg‐laying behavior in C. elegans (Kim et al, ), providing a mechanism by which it may mediate fecundity compensation. Interestingly, although hosts in the Biomphalaria glabrata–Schistosoma mansoni trematode system do not exhibit fecundity compensation during presumably stressful drought conditions, the parasites do ramp up offspring production (Gleichsner, Cleveland, & Minchella, ). Such a finding suggests that the connection between general stress and fecundity compensation can be complex in natural systems and that it can nevertheless be extended beyond hosts to parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Lines represent linear regressions for offspring produced as a function of infection intensity for infected females, calculated within each predator cue treatment, and shaded regions represent 95% confidence intervals. There was no significant relationship in the no predator cue treatment (p = .384) or early exposure treatment (p = .888), but a significant positive effect of infection intensity on number of offspring in the sustained exposure treatment (p = .018) studies have shown that, depending on the type and size of the predator, organisms may respond to predator cues by increasing reproduction (Gleichsner, Cleveland, & Minchella, 2016;Vale & Little, 2012). One possible explanation for the observed positive relationship between infection intensity and offspring production in infected females is that Daphnia may be able to sense infection intensity (and the corresponding survival costs) and increase their reproductive rate (at least over the short term).…”
Section: F I G U R Ementioning
confidence: 94%
“…In weeks four to seven post parasite exposure, snails from each group were transferred into well plates filled with 10 mL of corresponding salinity treatment solution and cercarial release was observed. After one hour under artificial light, 1 mL of mixed solution was drawn from each well, and the number of cercariae was counted for each snail [20]. Snails in which at least 10 cercariae were detected from the randomized 1 mL out of 10 mL were designated as infected.…”
Section: Methodsmentioning
confidence: 99%